Association of childhood maltreatment and adverse lifetime experiences with post-injury psychopathology: evidence from the China Severe Trauma Cohort - Shu Wen; Yu Zeng; Yueyao Xu; Shishi Xu; Wenwen Chen; Guanglin Wang; Wei Zhang; Huan Song (BMC Medicine)
Abstract Background Adverse life experiences have been associated with increased susceptibilities to psychopathology in later life. However, their impact on psychological responses following physical trauma remains largely unexplored. Methods Based on the China Severe Trauma Cohort, we conducted a cohort study of 2937 patients who were admitted to the Trauma Medical Center of West China Hospital between June 2020 and August 2023. Adverse life experiences, including childhood maltreatment (5 subtypes, measured by Childhood Trauma Questionnaire-Short Form) and adverse lifetime experiences (17 subtypes, by Life Events Checklist) were assessed. Generalized linear mixed models were used to examine the associations of childhood maltreatment and adverse lifetime experiences with symptoms of psychopathology measured at multiple time-points after the index injury (i.e., at recruitment, 1-, 3-, 6-, and 12-month follow-ups), adjusted for important confounders. We further stratified the analyses by level of genetic predisposition to a given psychological symptom quantified by polygenic risk score (PRS) based on publicly available GWAS summary statistics. Mediation analyses were performed to assess the role of adverse lifetime experiences in connecting childhood maltreatment and post-injury psychopathology. Results The mean age of participants was 47.95 years with a predominance of males (61.39%). During the whole follow-up period, the incidence of symptoms of stress-related disorders, anxiety, and depression was 13.86%, 29.89%, and 36.57%, respectively. We observed associations between the cumulative number of those studied adversities and increased risk of post-injury psychopathology, particularly stress-related disorder (odds ratio [OR] = 2.78, 95% confidence interval [CI] 1.87–4.12 for ≥ 2 vs no childhood maltreatment; 2.65 [1.67–4.20] for ≥ 4 vs 0–1 adverse lifetime experiences). By subtype, positive associations were observed for most studied life adversities, with the most pronounced estimates for childhood emotional abuse (ORs = 1.71–2.52) and lifetime life-threatening illness/injury (ORs = 1.87–2.89). We found basically comparable estimates among traumatized individuals with different PRSs for studied psychopathology. Moreover, adverse lifetime experiences may partially (mediation proportion: 22.52–27.48%) explain the associations between various childhood maltreatment and post-injury psychopathology. Conclusions Both childhood maltreatment and adverse lifetime experiences were associated with post-injury psychopathology, irrespective of genetic susceptibility. Such findings highlight the importance of close surveillance and timely psychological interventions for injury patients with adverse life experiences.